Prof dr J H Koekemoer as kerkman en akademikus - Merwe, P. J. van der (Hervormde teologiese studies, 2000)
Prof Dr J H Koekemoer in service of church and university. Prof Johannes Hendrik Koekemoer's career as minister of the Nederduitsch Hervormde Kerk started in 1960. In 1989 he became a full member and in 1992 Dean of the Faculty of Theology (Section A), Universiteit of Pretoria. This second part of his career ended on 31 December 1999 when he retired. He played a major role in the restructuring and amalgamation of the Faculty of Theology. The article reviews his work and contribution in both fields of church and university.